PERAN PROMOTIONAL MIX SEBAGAI VARIABEL MODERASI ORIENTASI PELANGGAN DAN ORIENTASI PESAING TERHADAP KINERJA PEMASARAN (Studi Empiris pada UKM Rumah Makan di Kabupaten Sragen) - Septiana Novita Dewi; Taupiq Nuzuli (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2017)
Increasingly fierce competition makes Small and Medium Enterprises (SMEs) restaurants are required to create the right strategy in creating consumer satisfaction by improving marketing performance. The existence of SMEs restaurants began unrivaled or even displaced by the business café or culinary stalls with a more varied and representative appearance. More and more restaurants are emerging illustrates the increasing level of competition in SMEs Restaurant, especially in Sragen regency. Looking at the phenomenon, the research team submitted research related to marketing strategy such as customer orientation, competitor orientation and promotional mix which is predicted to improve marketing performance of SME Restaurant in Sragen Regency. The population in this study is the owner or manager of SME Restaurant in Sragen regency in accordance with the criteria. The criterion of the owner or manager of SMEs being the population in this study is the data published by BPS as SMEs and in accordance with (Law No. 20 of 2008). A representative sample size for using Structural Equation Modeling (SEM) analysis is at least five times the number of parameters. (Hair, 2004; Ferdinand, 2005). In this study the number of parameters is 20 so that the minimum sample size is: 20 x 5 = 100. The sampling technique in this study uses convenience sampling. The results showed that customer orientation has a positive and significant influence on marketing performance. The competitor's orientation has a positive and significant impact on marketing performance. Promotional mix moderates the effect of customer orientation on marketing performance. Promotional mix moderates the influence of competitors' orientation on marketing performance.